Pengaruh Kinerja Guru Terhadap Hasil Belajar Siswa di Sekolah Dasar - Wardany, Elfina Pramesti Kusuma; Rigianti, Henry Aditia (Institut Agama Islam Daruttaqwa Gresik, 2023)
This research is a descriptive study that aims to investigate the impact of teacher work quality on student learning achievement at SD Negeri Durensawit. The participants involved in the observation consisted of two groups: teachers and students. The teacher participants had similar educational scales but diverse teaching observations. All participating teachers had an undergraduate educational background. This study used questionnaires and learning achievement tests as data collection instruments. Data from the questionnaire was analyzed using a quantitative approach by calculating the exposure for each criterion contained in the survey. Meanwhile, the data from the interviews were analyzed descriptively by interpreting the findings. The results of this study evaluated that (1) teacher performance has a significant influence on improving students' mathematics learning outcomes, (2) the higher the efforts made by educators in planning, conducting, and concluding the learning process, the greater the chance for educators to improve student’s learning outcomes, and (3) teachers' educational experience also plays an important role in improving students' learning outcomes.